2019
DOI: 10.1016/j.ajog.2018.08.032
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of opportunistic salpingectomy vs tubal ligation at the time of cesarean delivery

Abstract: Bilateral tubal ligation and bilateral opportunistic salpingectomy with cesarean delivery are both cost-effective strategies for permanent sterilization and ovarian cancer risk reduction. Although salpingectomy and tubal ligation are both reasonable strategies for cesarean patients seeking permanent sterilization and cancer risk reduction, threshold analyses indicate that the risks and benefits of salpingectomy with cesarean delivery need to be better defined before a preferred strategy can be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 61 publications
1
15
0
Order By: Relevance
“…Six studies [ 34 , 35 , 46 , 49 , 50 , 51 ] included women who opted for permanent sterilisation; two [ 49 , 51 ] of them assessed permanent sterilisation in the context of a caesarean section. In the four (non-caesarean section) studies, only Dilley et al [ 34 ] incorporated a disutility of 0.77 for surgical complication over one year.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Six studies [ 34 , 35 , 46 , 49 , 50 , 51 ] included women who opted for permanent sterilisation; two [ 49 , 51 ] of them assessed permanent sterilisation in the context of a caesarean section. In the four (non-caesarean section) studies, only Dilley et al [ 34 ] incorporated a disutility of 0.77 for surgical complication over one year.…”
Section: Resultsmentioning
confidence: 99%
“…In the two studies evaluating the cost-effectiveness of OBS in the context of caesarean, they both found that OBS was cost-effective, with an ICUR of $28,109/QALY [ 49 ] and $24,490/QALY [ 51 ] compared to tubal ligation. OBS for permanent sterilisation during caesarean section could prevent one OC case in every 261/589 women, one OC-death in every 437/770 women and one unintended pregnancy in every 400/1134 women compared with tubal ligation [ 49 , 51 ]. The two models did not consider disutility from OBS or tubal ligation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, PBS in women undergoing surgical sterilization (N=4, (31)(32)(33)(34)) was reported to be cost-effective with ICURs ranging from 7,000 to 18,000 Euros/QALY (ICER range: 4,000-12,000 Euros/LYG) compared to surgical sterilization alone.…”
Section: (A) Ovarian Cancer Screeningmentioning
confidence: 99%
“…In 2015, an American College of Obstetricians and Gynecologists Committee Opinion recommended that obstetricians should discuss the possible risk-reducing benefits of bilateral salpingectomy with patients who wish to have permanent contraception ( 13 ) . However, the embracement of this strategy at the time of cesarean delivery for pregnant women who desire permanent sterilization has not been widely adopted, probably due to a lack of available data including the surgical and psychological data in this setting ( 14 ) . By 2017, the overall proportion of salpingectomies in patients who underwent a permanent contraception procedure was reported to be as high as 61.5%, in a nationwide data analysis ( 15 ) .…”
Section: Discussionmentioning
confidence: 99%